ASSESSMENT OF GENETIC DIVERSITY AND POPULATION STRUCTURE AMONG NORTH-EASTERN AND NORTH-WESTERN HIMALAYAN MAIZE LANDRACES USING MORPHOLOGICAL AND MOLECULAR MARKERS - NISHA PALIA; MANEET RANA; AKSHITA AWASTHI; REENA KUMARI; ZAHOOR DAR; SWARAN LATA (The Bioscan, 2020)
Genetic diversity among 60 maize genotypes was determined using morphological and SSR markers. Sufficient genetic variability was observed for all the twelve traits studied during present investigation. Estimates of phenotypic coefficient of variation (PCV) were higher than genotypic coefficient of variation (GCV) for all the traits. PCV and GCV was highest for grain yield per plant (42.76%, 34.37 %) followed by 100 gram weight (17.79%, 17.37%), respectively. The broad sense heritability was found to be high (>80%) for most of the traits except for grain yield per plant (64.60%). High PCV, GCV and GA were observed for grain yield per plant with moderate heritability. Grains per row revealed high direct contribution towards grain yield per plant. Cob placement height, cob length and cob girth contributed most towards genetic divergence. At molecular level, 20 SSR primers amplified a total of 52 polymorphic alleles with an average of 2.60 alleles per primer. Mean polymorphic information content was 0.31 showing a moderate level of SSR polymorphism. Cluster analysis differentiated 60 maize landraces into four major clusters. During present studies few genetically divergent landraces (LM-18-08, LM-19-07, LM-14-11, LM- 01-08 and LM-11-11) could be employed for their systematic and efficient use in breeding programs.